2013
DOI: 10.1094/pdis-01-13-0048-re
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Grapevine Leafroll-Associated Viruses in China

Abstract: To characterize the prevalence of viruses associated with grapevine leafroll disease in China, 249 grapevine (Vitis spp.) samples (86 popular cultivars and a rootstock) from 19 provinces and regions were collected and tested for Grapevine leafroll-associated virus 1 (GLRaV-1), GLRaV-2, GLRaV-3, GLRaV-4, and GLRaV-4 strain 5 by SYBR Green real-time reverse-transcription polymerase chain reaction (RT-PCR), and RT-PCR and sequencing. GLRaV-3 was found in 100% of the samples while GLRaV-1, GLRaV-2, and GLRaV-4 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 27 publications
2
21
1
Order By: Relevance
“…In this study, PCR and nPCR were used to detect GLRaV-1 in 134 grapevine samples, and the results showed that nPCR can detect more GLRaV-1 isolates than conventional PCR. The overall incidence of GLRaV-1 was 36.4 % (48/132), which was far higher than what was reported previously [14]. Thus, the use of RT-nPCR can largely increase the detection sensitivity, and this method could be used as an alternative method when no real-time PCR device is available.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In this study, PCR and nPCR were used to detect GLRaV-1 in 134 grapevine samples, and the results showed that nPCR can detect more GLRaV-1 isolates than conventional PCR. The overall incidence of GLRaV-1 was 36.4 % (48/132), which was far higher than what was reported previously [14]. Thus, the use of RT-nPCR can largely increase the detection sensitivity, and this method could be used as an alternative method when no real-time PCR device is available.…”
Section: Discussionmentioning
confidence: 69%
“…[1] and one of the main causative agents of GLD in other countries [6,9,15,17,22]. Recently, a survey in China showed that GLD was widespread and that GLRaV-1 was the most common agent after GLRaV-3 [14]. Using untested grapevine materials for propagating or grafting increases the risk of spreading GLD; therefore, efficient detection of GLRaV-1 and -3 is urgently required for certification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many grape-growing countries and regions, virus surveys have been conducted on grapevines, for example, in Argentina (Volpe et al, 2010), Chile (Fiore et al, 2011), China (Liu et al, 2013), the United States (Jones et al, 2015), Slovakia, the Czech Republic (Glasa et al, 2015) and in two regions of northeastern Brazil (Catarino et al, 2015), in which the incidence of viruses was highly variable, depending on the viral species, grapevine cultivars and …”
Section: Incidence Of Viruses and Viroid In Grapevinesmentioning
confidence: 99%
“…Recently, a survey showed that GLD is widespread in China, and GLRaV‐2 was identified as one of the main agents in grapevines showing GLD (Liu et al. ). However, surveys of GLRaV‐2 in symptomless grapevine samples, especially in rootstocks, are limited.…”
Section: Introductionmentioning
confidence: 99%